2003
DOI: 10.1091/mbc.e02-12-0809
|View full text |Cite
|
Sign up to set email alerts
|

Selective Caveolin-1–dependent Endocytosis of Glycosphingolipids

Abstract: We studied the endocytosis of fluorescent glycosphingolipid (GSL) analogs in various cell types using pathway-specific inhibitors and colocalization studies with endocytic markers and DsRed caveolin-1 (cav-1). Based on inhibitor studies, all GSLs tested were internalized predominantly (Ͼ80%) by a clathrin-independent, caveolar-related mechanism, regardless of cell type. In addition, fluorescent lactosylceramide (LacCer) colocalized with DsRed-cav-1 in vesicular structures upon endocytosis in rat fibroblasts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
252
4
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(271 citation statements)
references
References 44 publications
(63 reference statements)
12
252
4
3
Order By: Relevance
“…We were unable to detect significant inhibition of CTB internalization in our Dyn2 KO cells ( Figure 5A), although we confirmed findings of others that the overexpression of a dominant negative mutant Dyn2K44A blocks CTB uptake in our fibroblasts ( Figure 5B). Similar results were obtained using BODIPY-LacCer, which is reported to be a more specific probe for caveolae-mediated endocytosis (Singh et al, 2003; Figure 5C). Because overexpressed Dyn2K44A will dominantly interfere with the function of both endogenous Dyn2 and -1 isoforms, the more potent effect of dominantnegative overexpression suggests that the remaining Dyn1 may be sufficient to support CTB uptake in the Dyn2 KO cells.…”
Section: Dyn2 Is Required For Pdgf-stimulated Macropinocytosis But Nsupporting
confidence: 85%
“…We were unable to detect significant inhibition of CTB internalization in our Dyn2 KO cells ( Figure 5A), although we confirmed findings of others that the overexpression of a dominant negative mutant Dyn2K44A blocks CTB uptake in our fibroblasts ( Figure 5B). Similar results were obtained using BODIPY-LacCer, which is reported to be a more specific probe for caveolae-mediated endocytosis (Singh et al, 2003; Figure 5C). Because overexpressed Dyn2K44A will dominantly interfere with the function of both endogenous Dyn2 and -1 isoforms, the more potent effect of dominantnegative overexpression suggests that the remaining Dyn1 may be sufficient to support CTB uptake in the Dyn2 KO cells.…”
Section: Dyn2 Is Required For Pdgf-stimulated Macropinocytosis But Nsupporting
confidence: 85%
“…To confirm that cav-2 mutants have defects in apical trafficking, we exposed animals to BODIPY-tagged lactosylceramide (BODIPY FL C5 LacCer, Invitrogen). It has previously been shown that glycosphingolipid analogues are internalized through a predominantly caveolin-dependent route in human cells (Singh et al, 2003;Mayor and Pagano, 2007;Singh et al, 2007). In wild-type animals exposed to 5 M BODIPY-LacCer for 2 h, fluorescent LacCer accumulates in a punctate pattern in the intestine.…”
Section: Cav-2 Mutants Exhibit Altered Apical Traffickingmentioning
confidence: 96%
“…By contrast, the preferential uptake of glycolipids by caveolae [31] requires lipid-based aggregation [32]. Glycolipids are used as endocytotic receptors by toxins, viruses and bacteria.…”
Section: Selective Endocytosismentioning
confidence: 99%